Startlement : new and selected poems - Limón, Ada (Milkweed Editions, 2025)
"Drawing from six previously published books--including widely acclaimed collections The Hurting Kind, The Carrying, and Bright Dead Things--as well as vibrant new work, Startlement exalts the mysterious. With a tender curiosity, Ada Limón wades into potent unknowns--the strangeness of our brief human lives, the ever-changing nature of the universe--and emerges each time with new revelations about our place in the world... From the chaos of youthful desire, to the waxing of love and loss, to the precarity of our environment, to the stars and beyond, Limón's poetry bears witness to the arc of all we know with patient lyricism and humble wonder."--Amazon.com